ACTIVE SUPPRESSION OF IMMUNOGLOBULIN ALLOTYPE SYNTHESIS : I. CHRONIC SUPPRESSION AFTER PERINATAL EXPOSURE TO MATERNAL ANTIBODY TO PATERNAL ALLOTYPE IN (SJL x BALB/c)F(1) MICE - Jacobson, E. B. (The Rockefeller University Press, 1972)
Long-term (chronic) allotype suppression, previously reported only in rabbits, is shown here to occur in at least one strain combination of mice as well. Close to 50% of the offspring of SJL (Ig(b)) males mated to BALB/c (Ig(a)) females immunized against the paternal allotype were found to be suppressed for Ig-1b (γG(2a)) at 6 months of age. These mice are called "chronically" suppressed. The percentage of offspring in this strain combination suppressed for the paternal allotype at 8 wk of age is the same as that seen in an earlier strain combination tested, [(C57 x BALB/c)F(1)], in which all mice recover from suppression by 10–12 wk. After 8 wk, two distinct patterns of long-term (chronic) suppression emerge in (SJL x BALB/c)F(1) mice: a small number of these mice never produce detectable amounts of Ig-1b throughout their lives, while the majority produce detectable Ig-1b sporadically, sometimes over a period of several weeks, the level of which eventually falls below detectability. Attempts to "cure" suppression by destroying the existent lymphoid population and forcing endogenous repopulation in chronically suppressed animals were unsuccessful. Furthermore, attempts to restore Ig-1b production by injection of cells from syngeneic Ig(a)/Ig(b) donors into irradiated, chronically suppressed recipients were also unsuccessful, although the same cell inocula, when injected into irradiated BALB/c (Ig(a)/Ig(a)) mice produced high levels of gamma globulin carrying the allotype. These results suggest that long-term allotype suppression resulting from perinatal exposure of offspring to specific anti-allotype antibody (anti-Ig-1b), is not due merely to an absence of Ig-1b-producing cells or their progenitors, but appears to be an active process, which dominates physiologically over normal production.